Penerapan Terapi Teka-Teki Silang untuk Meningkatkan Fungsi Kognitif pada Lansia di Panti Werdha - Ezra Naomi Theresia; Lilik Pranata; Bangun Dwi Hardika (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Individuals over the age of 60 are vulnerable to a decline in body functions, including nervous system functions that can lead to cognitive impairment and dementia. This condition can cause the elderly to be unable to perform activities, thereby impacting their well-being and happiness. One effort to overcome this is through crossword puzzle therapy to stimulate and improve cognitive function. To implement research-based nursing actions for the elderly with decreased cognitive function. The design used in this final nursing thesis is a case study with an intervention involving crossword puzzle therapy. The number of respondents was four, with the intervention conducted over one week at a frequency of twice daily, starting from June 22–28, 2025, and continuing from June 28–July 5, 2025, at the Dharma Bhakti Elderly Care Home KM 7 Palembang. After undergoing crossword puzzle therapy for one consecutive week, the four elderly participants showed changes in their MMSE scores at the final meeting: Mrs. L from 20 to 22, Mrs. M from 18 to 20, Mrs. A from 21 to 22, and Mrs. N from 22 to 23. Here was an improvement in cognitive function before and after crossword puzzle therapy was administered to the four participants. The application of this EBP is expected to add information about the provision of crossword puzzle therapy in the elderly with cognitive decline.